Adaptation of an additively manufactured reactor concept for catalytic methanation with in-situ tar co-reforming of biogenic syngas - Müller, Jakob; Feldner, Alexander; Markthaler, Simon; Treiber, Peter; Karl, Jürgen (Chemical Engineering Journal Advances, 2025)
Keywords: Tar removal; Heat pipes; Reactor design; Additive manufacturing; 3D-printing; Finite element analysis; Catalytic methanation

Design and Implementation of an Additively Manufactured Reactor Concept for the Catalytic Methanation - Hauser, Alexander; Neubert, Michael; Feldner, Alexander; Horn, Alexander; Grimm, Fabian; Karl, Jürgen (Applied Sciences, 2022)
The methanation process is discussed as one way to chemically store renewable energy in a future energy system. An important criterion for its application is the availability of compact, low-cost reactor concepts with high conversion rates for decentralized use where the renewable energy is produced. Current research focuses on the maximization of the methane yield through improved temperature control of the exothermic reaction, which attempts to avoid both kinetic and thermodynamic limitations. In this context, traditional manufacturing methods limit the design options of the reactor and thus the temperature control possibilities. The use of additive manufacturing methods removes this restriction and creates new freedom in the design process. This paper formulates the requirements for a novel methanation reactor and presents their implementation to a highly innovative reactor concept called ‘ADDmeth’. By using a conical reaction channel expanding from Ø 8 to 32 mm, three twisted, expanding heat pipes (Ø 8 mm in evaporation zone, Ø 12 mm in condenser zone) and a lattice structure for feed gas preheating and mechanical stabilization of the reactor, the design explicitly exploits the advantages of additive manufacturing. The reactor is very compact with a specific mass of 0.36 kg/kW and has a high share of functional volume of 52%. The reactor development was accompanied by tensile tests of additively manufactured samples with the used material 1.4404 (316 L), strength calculations for stability verification and feasibility studies on the printability of fine structures. Ultimate tensile strengths of up to 750 N/mm2 (at room temperature) and sufficiently high safety factors of the pressure-loaded structures against yielding were determined. Finally, the paper presents the manufactured bench-scale reactor ADDmeth1 and its implementation.
CRIS-Team Scopus Importer:2022-10-07
Keywords: additive manufacturing; catalytic methanation; conic reaction channel; heat pipes; reactor design

Katalytische und biologische Direktmethanisierung von Biogas im Rahmen der Forschungsprojekte Power-to-Biogas, FlexBiomethane und IntenseMethane - Feldner, Alexander; Markthaler, Simon; Treiber, Peter; Karl, Jürgen (Statuskonferenz Bioenergie 2023, 2023)

Self-sufficient hydrogen production from biogas by reformingand CO combustion - Feldner, Alexander; Treiber, Peter; Karl, Jürgen (75. Jahrestreffen der DECHEMA-Fachgruppe Hochtemperaturtechnik, 2023)

Utilization of Synthetic Steel Gases in an Additively Manufactured Reactor for Catalytic Methanation - Hauser, Alexander; Feldner, Alexander; Treiber, Peter; Grimm, Fabian; Karl, Jürgen (Sustainability, 2023)
The path to European climate neutrality by 2050 will require comprehensive changes in all areas of life. For large industries such as steelworks, this results in the need for climate-friendly technologies. However, the age structure of existing steelworks makes transitional solutions such as carbon capture, utilization and storage (CCUS) necessary as short-term measures. Hence, a purposeful option is the integration of technical syntheses such as methanation into the overall process. This work summarizes hydrogen-intensified methanation experiments with synthetic steel gases in the novel additively manufactured reactor ‘ADDmeth1’. The studies include steady-state operating points at various reactor loads. Blast furnace gas (BFG), basic oxygen furnace gas (BOFG) and three mixtures of these two gases serve as carbon sources. The methanation achieved methane yields of 93.5% for BFG and 95.0% for BOFG in the one-stage once-through setup. The results suggest a kinetic limitation in the case of BFG methanation, while an equilibrium limitation is likely for BOFG. There is a smooth transition in all respects between the two extreme cases. The reaction channel inlet temperature (Formula presented.) showed a large influence on the reactor ignition behavior. By falling below the threshold value, a blow-off occurred during experimental operation. By means of a simulation model, practical operating maps were created which characterize permissible operating ranges for (Formula presented.) as a function of the gas composition and the reactor load.
CRIS-Team Scopus Importer:2023-05-26
Keywords: BFG; BOFG; by-product gas; catalytic methanation; ignition behavior; simulation; temperature profiles